Spatial Separation of Cocatalysts on Z‐Scheme Organic/Inorganic Heterostructure Hollow Spheres for Enhanced Photocatalytic H2 Evolution and In‐Depth Analysis of the Charge‐Transfer Mechanism. Issue 4 (11th March 2022) - Moon, Hyun Sik; Hsiao, Kai‐Chi; Wu, Ming‐Chung; Yun, Yongju; Hsu, Yung‐Jung; Yong, Kijung
Abstract: A Z‐scheme heterojunction with spatially separated cocatalysts is proposed for overcoming fundamental issues in photocatalytic water splitting, such as inefficient light absorption, charge recombination, and sluggish reaction kinetics. For efficient light absorption and interfacial charge separation, Z‐scheme organic/inorganic heterojunction photocatalysts are synthesized by firmly immobilizing ultrathin g‐C3 N4 on the surface of TiO2 hollow spheres via electrostatic interactions. Additionally, two cocatalysts, Pt and IrO x, are spatially separated along the Z‐scheme charge‐transfer pathway to enhance surface charge separation and reaction kinetics. The as‐prepared Pt/g‐C3 N4 /TiO2 /IrO x (PCTI) hollow sphere photocatalyst exhibits an exceptional H2 evolution rate of 8.15 mmol h −1 g −1 and a remarkable apparent quantum yield of 24.3% at 330 nm in the presence of 0.5 wt% Pt and 1.2 wt% IrO x cocatalysts on g‐C3 N4 and TiO2, respectively. Photoassisted Kelvin probe force microscopy is used to systematically analyze the Z‐scheme charge‐transfer mechanism within PCTI. Furthermore, the benefits of spatially separating cocatalysts in the PCTI system are methodically investigated in comparison to randomly depositing them. This work adequately demonstrates that the combination of a Z‐scheme heterojunction and spatially separated cocatalysts can be a promising strategy for designing high‐performance photocatalytic platforms for solar fuel production. Abstract : A Z‐scheme heterojunction hollow sphere with spatially separated cocatalysts is proposed to overcome the fundamental limitation in photocatalytic water splitting. The Z‐scheme heterojunction effectively stimulates interfacial charge transfer while retaining high redox power, whereas the spatially separated cocatalysts stimulate surface charge separation. Their synergistic effect results in an exceptional photocatalytic H2 evolution performance of 8.15 mmol g −1 h −1 .